Human myelomonocytic cells express an inhibitory receptor for classical and nonclassical MHC class I molecules. - Colonna, M; Samaridis, J; Cella, M; Angman, L; Allen, R; O'Callaghan, C; Dunbar, R; Ogg, G; Cerundolo, V; Rolink, A (1998)
Leukocyte activation can be negatively regulated by inhibitory receptors specific for MHC class I molecules. While one inhibitory receptor, Ig-like transcript 2 (ILT2), is expressed by all lymphoid and myelomonocytic cell types, other receptors display a more selective tissue distribution. Here we characterize an inhibitory receptor, termed ILT4, which is selectively expressed in monocytes, macrophages, and dendritic cells (DCs), binds classical class I molecules and the nonclassical class I molecules HLA-G, and transduces negative signals that can inhibit early signaling events triggered by stimulatory receptors. ILT4 may control inflammatory responses and cytotoxicity mediated by myelomonocytic cells and may modulate their Ag-presenting functions, focusing immune responses to microbial challenges and avoiding autoreactivity.